An Evaluation of the 4-H Health Rocks Program: Implications for Program Improvement. (March 2013) - Self, Carlton; Morgan, A. Christian; Fuhrman, Nicholas E.; Navarro, Maria
The National 4-H Council developed the Health Rocks substance abuse educational program to prevent youth from engaging in risky behaviors. The program was presented in 2010 to more than 8, 000 middle school youth in Georgia. A post-then-pre evaluation was conducted with youth who completed 10 hours of instruction to determine if changes in youth knowledge, beliefs/attitudes, skills, and behavioral intentions occurred during the course of the program. This study sought to measure the impact of the program and critically evaluate the questionnaire used. The data revealed statistically significant increases in knowledge, beliefs/attitudes, skills, and behavioral intentions of participating youth. Suggestions for improvement of the questionnaire included utilizing questions that are more specific to the curriculum and adding questions to measure the influence of peer pressure.